The ectodysplasin pathway: from diseases to adaptations - Sadier, Alexa; Viriot, Laurent; Pantalacci, Sophie; Laudet, Vincent (Trends in genetics, 2014)
•The Ectodysplasin pathway controls ectodermal appendages in vertebrates.•The core of the pathway contains three main gene products: EDA, EDAR, and EDARADD.•Mutation of the pathway causes anhidrotic/hypohidrotic ectodermal dysplasia in humans.•The EDA pathway has been associated with specific adaptations in fish and humans. The ectodysplasin (EDA) pathway, which is active during the development of ectodermal organs, including teeth, hairs, feathers, and mammary glands, and which is crucial for fine-tuning the developmental network controlling the number, size, and density of these structures, was discovered by studying human patients affected by anhidrotic/hypohidrotic ectodermal dysplasia. It comprises three main gene products: EDA, a ligand that belongs to the tumor necrosis factor (TNF)-α family, EDAR, a receptor related to the TNFα receptors, and EDARADD, a specific adaptor. This core pathway relies on downstream NF-κB pathway activation to regulate target genes. The pathway has recently been found to be associated with specific adaptations in natural populations: the magnitude of armor plates in sticklebacks and the hair structure in Asian human populations. Thus, despite its role in human disease, the EDA pathway is a ‘hopeful pathway’ that could allow adaptive changes in ectodermal appendages which, as specialized interfaces with the environment, are considered hot-spots of morphological evolution.